Heat recovery enhancement in HENs using a combinatorial approach of paths combination and process streamsâ temperature flexibility - Osman, A. (Elsevier B.V., 2016)
Current economic uncertainties and tighter environmental regulations has led industries to consider energy conservation projects more seriously. In this paper, the option of varying the process stream temperature has been suggested as a mean of increasing heat recovery for heat exchanger networks (HEN). Alternatives are generated and assessed using a developed approach. Essentially, the approach involves systematic steps in varying the Hot and/or Cold streamsâ temperature for each stream in a way that increases the heat recovery approach temperature (HRAT), thus allowing more heat to be recovered. Using the combinatorial method of paths combinations, the adjustment of heat loads for hot and cold utilities from the heat load shifting through the heat exchanger network could be made and assessed accordingly. The changes in temperature made to the streams while exploring each alternative has to be kept within small magnitude i.e., around 1â5Â Â°C. A user friendly computer program has been developed for performing the approach in view of the significant number of iterations required. An example is used in this paper to demonstrate the application of the developed approach. Â© 2016 The Authors